PENGARUH SENAM LANSIA TERHADAP KEBUGARAN JASMANI WARGA PERUMAHAN PONDOK PINANG KELURAHAN LUBUK BUAYA KECAMATAN KOTO TANGAH KOTA PADANG - Mardius, Ali; astuti, yuni (LPPM Undiksha, 2017)
Problems in this study are still many people who do not have good physical fitness. This study aims to determine the influence of elderly gymnastics on the physical fitness of residents Pondok Pinang Village Lubuk Buaya Sub-District Koto Tangah Padang City. The sample in this research is resident of lodge of pinang numbered as many as 18 people. The instrument used to measure peoples physical fitness is 2.4 km. Data were analyzed by using t-test different mean. Based on the results of data analysis, it was found that elderly gymnastics had a significant effect on physical fitness, because it was found thitung = 5.35 > ttable = 2.11 and it was proved that there was a difference of mean physical fitness before treatment (preliminary test) Is 22.58 and mean after treatment is given (final test) is 18,73, it means there is increase 3,85 to physical fitness